The Language of the Linguistic Expert’s Opinion - V. O. Kuznetsov (Теория и практика судебной экспертизы)
The article is devoted to the language of linguistic expert’s opinion as one of aspects of language problem of forensic examination and as a part of general theoretical block in structure of modern forensic expertise. It is stated that the expert’s opinion is a heterogeneous procedural document by its style since it is combining elements of both official and scientific style of speech. A form and a content of constituent parts of the linguistic expert’s opinion are considered from perspective of language. These parts are: introduction, research part and conclusion. It is determined that compliance with principles of drawing up the expert’s opinion and responsible attitude of the expert to the choice of linguistic means when describing process of study will make this procedural document a strong argument when used as an evidence.